1996
DOI: 10.1177/089686089601600309
|View full text |Cite
|
Sign up to set email alerts
|

The Japanese National Registry Data on Pediatric Capd Patients: A Ten-Year Experience a Report of the Study Group of Pediatric Pd Conference

Abstract: Objective Over the past 10 years, we have collected data on pediatric patients less than 16 years of age from the National Registry of CAPD (continuous ambulatory peritoneal dialysis). We present our experience with this population. Design The database details the patient number, age, weight, height, outcome, cause of death, reason for terminating CAPD therapy, peritonitis, and catheter survival. Patients Of the 434 patients (239 males, 195 females), 37 patients (8.5%) were under 1 year of age and 164 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 3 publications
4
23
1
Order By: Relevance
“…Similar to previous reports, the current NAPRTCS report reveals an inverse relationship between the age of the patient and peritonitis rate, with the youngest patients (<1 year) having an annualized rate of 0.86 (one infection every 13.9 months), while the adolescents (>12 years) have a rate of 0.61 (one infection every 19.8 months). These rates were derived from clinical experience in the USA and are comparable to what has been documented in European centers, but poorer than the exceptionally low rates (one infection every 28.6 months) found among Japanese children [ 23 25 ].…”
Section: Incidence Of Peritonitissupporting
confidence: 58%
“…Similar to previous reports, the current NAPRTCS report reveals an inverse relationship between the age of the patient and peritonitis rate, with the youngest patients (<1 year) having an annualized rate of 0.86 (one infection every 13.9 months), while the adolescents (>12 years) have a rate of 0.61 (one infection every 19.8 months). These rates were derived from clinical experience in the USA and are comparable to what has been documented in European centers, but poorer than the exceptionally low rates (one infection every 28.6 months) found among Japanese children [ 23 25 ].…”
Section: Incidence Of Peritonitissupporting
confidence: 58%
“…However, the present screening program for proteinuria and hematuria make it difficult to detect congenital kidney and urinary tract abnormalities at an early stage. Congenital kidney and urinary tract abnormalities account for 30% of the pediatric primary renal diseases that cause end‐stage renal insufficiency in Japan 2 . The North American Pediatric Renal Transplant Cooperative Study reported that nearly two‐thirds of children and adolescents with chronic renal insufficiency had structural anomalies of the kidneys and urinary tract 3 .…”
mentioning
confidence: 99%
“…Honda et al . from the Japanese Registry in Pediatric CAPD patients documented better catheter survival with the double‐cuff vs. single‐cuff catheter (82.2% vs. 69.0% at 1 years and 54.2% vs. 43.2% at 2 years) but did not comment on the difference in peritonitis between the two groups in a retrospective review of 434 paediatric PD patients 11 …”
Section: Suggestions For Clinical Carementioning
confidence: 94%
“…International Society for Peritoneal Dialysis 1998: Convincing data exist to indicate that the double‐cuff catheter is preferable to the single‐cuff catheter, therefore a double‐cuff configuration is recommended (the data they quote is retrospective data for both peritonitis 9–11 and for catheter survival time 19,20 ). A downward‐directed exit may decrease the risk of catheter‐related peritonitis.…”
Section: What Do the Other Guidelines Say?mentioning
confidence: 99%